Performance of japanese quails fed feeds containing different corn and limestone particle sizes - Berto, da [UNESP] (2007)
This study aimed at evaluating performance and egg quality of Japanese quails fed feeds containing different corn and limestone particle sizes. A total number of 648 birds in the peak of production was distributed in a random complete block experimental design, using a 2x3 factorial arrangement (2 corn particle sizes and 3 limestone particle sizes). Birds were designated to one of two blocks, with six replicates of 18 birds each. Mean geometric diameter (MGD) values used were 0.617mm and 0.723mm (corn fine and coarse particle sizes, respectively), and 0.361mm, 0.721mm, and 0.947mm (limestone fine, intermediate and coarse particle sizes, respectively). The following treatments were applied: T1: fine corn feed, with 100% fine limestone; T2: fine corn feed, with 50% fine limestone and 50% intermediate limestone; T3: fine corn feed, with 50% fine limestone and 50% coarse limestone; T4: coarse corn feed, with 100% fine limestone; T5: coarse corn feed, with 50% fine limestone and 50% intermediate limestone; T6: coarse corn feed, with 50% fine limestone and 50% coarse limestone. The experiment lasted 112 days, consisting of 4 cycles of 28 days. No significant interaction was observed among corn and limestone particle sizes for any of the analyzed parameters. There were no significant effects (p>0.05) of the tested corn particle sizes on quail performance or egg quality. There were significant (p<0.05) isolated effects of limestone particle size only on the percentage of cracked eggs, which was reduced when birds fed 50% coarse limestone (0.947mm) and 50% fine limestone (0.361mm) as compared to those fed 100% fine limestone. Therefore, the inclusion of 50% coarse limestone (0.947mm) is recommended for quail egg production.